The Effect of Workload and Autonomy on Organizational Commitment with Job Satisfaction as an Intervening Variable in Permanent Lecturers at Hang Tuah University Surabaya - Ria Fitriana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine the effect of workload and autonomy on organizational commitment with job satisfaction as an intervening variable. This research was conducted at Hang Tuah University Surabaya with 64 permanent lecturers as respondents. Data were collected through a Likert scale 1-5 questionnaire given to respondents and several supporting documents from Hang Tuah University Surabaya. In this study, the data was processed using the PLS-SEM method with WARP-PLS as the analysis tool. The results obtained indicate that the workload has no significant effect on job satisfaction; autonomy has a significant effect on job satisfaction; job satisfaction has a significant effect on organizational commitment; workload has a significant effect on organizational commitment; autonomy has a significant effect on organizational commitment